Optimal distributed coding schemes for energy efficiency in the fading relay channel - Parzysz, F.; Vu, M. H.; Gagnon, F. (2012 IEEE International Conference on Communications (ICC), 2012)
We propose three energy-optimal distributed schemes for the half-duplex relay channel with block fading to maintain a desired source rate. We consider both network energy consumption and consumption of the relay alone, assuming only local channel knowledge. Then, we combine both into a generalized distributed energy-efficient scheme. In these schemes, the source uses message splitting and allocates resources dynamically, such that direct transmission, decode-forward or partial decode-forward is performed at each block, depending on the channel quality. The optimal distributed power allocation is computed from the corresponding centralized scheme by using an estimate of the relay consumption. Compared to decode-forward with no message splitting as often used in distributed designs, the proposed schemes significantly decrease the peak power and provide up to 15% average energy gain for the network consumption and a minimum of 3.3dB gain for the relay consumption.